Ne pas s'avouer vaincu - Arbizu, Susana; Belin, Henri (France, 2012)
Daniel Serrano is a 91-year-old Spanish Republican living in exile in Bobigny, France. This film follows his attempts to clear the name of his brother Eudaldo, who was shot in 1941 after the Spanish Civil War. Daniel comes to realize that his native village of Toledo is still heavily influenced by its Socialist and Francoist past, which makes it difficult for Daniel to gain redemption for his brother.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films